Coalescence dynamics of nanofluid droplets in T-junction microchannel. (16th January 2023) - Deng, Yanjun; Zhu, Chunying; Fu, Taotao; Ma, Youguang
Highlights: Effect of nanoparticles on droplet coalescence in a microchannel was investigated. Droplet coalescence efficiency in the presence of nanoparticles was calculated. Variation of the droplet contact time and liquid film drainage time were studied. A new prediction model for critical condition of droplet coalescence was proposed. Abstract: The effect of nanoparticles on droplet coalescence in microchannel was investigated experimentally. The interaction between acid-functionalized nanoparticles and polymers with complementary terminal functional groups facilitates the adsorption of particles at the oil–water interface. Three flow patterns were observed: squeezing coalescence, decompression coalescence and non-coalescence. The presence of nanoparticles significantly reduces the droplet coalescence percentage, and stable droplets could be obtained when the particles concentration increased to 1%. Furthermore, it was found that the film drainage time of squeezing coalescence was independent of the nanoparticles concentration. However, the film drainage time of decompression coalescence increases with nanoparticles concentration. Taking the influence of nanoparticles on the film drainage time into consideration, a new prediction model was proposed. Coupling the droplet contact time with the film drainage time, the critical capillary number for droplet coalescence was obtained. This work could provide important data and technical support for the application of nanoparticle-stabilized emulsions.